1983
DOI: 10.1080/00102208308923637
|View full text |Cite
|
Sign up to set email alerts
|

Surface Growth of Soot Particles in Premixed Ethylene/Air Flames

Abstract: The surface growth rate of soot increases steeply with increasing equivalence ratio. We have found that the increased growth rate is accounted for primarily by the increased surface area available for growth rather than by increased concentrations of surface growth species. We have shown thai the surface growth species are not depleted by the process of surface growth. Our data suggest that the surface growth seen in our flames can be accounted for primarily by reaction of acetylene with the soot particles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
57
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(71 citation statements)
references
References 31 publications
11
57
1
Order By: Relevance
“…j , where j is the order of the reaction with respect to C 2 H 2 (76). The range of values of the specific surface growth rates found here are in accord with the typical data reported in the previous literature (77).…”
Section: Fig 2 Dissymmetry Ratiosupporting
confidence: 91%
“…j , where j is the order of the reaction with respect to C 2 H 2 (76). The range of values of the specific surface growth rates found here are in accord with the typical data reported in the previous literature (77).…”
Section: Fig 2 Dissymmetry Ratiosupporting
confidence: 91%
“…The material properties used in the calculation are found in Table IV of [2]. Soot is assumed to be composed of carbon only and its density is chosen to be 1.8 g / cm 3 [38]. In this figure, the solid lines are calculated using ϵ 0.9 for the Waldmann thermophoretic velocity, a value traditionally used in computing the thermophoretic velocity [9,18] and the drag force [19,20].…”
Section: Thermophoretic Velocitymentioning
confidence: 99%
“…Recently, the roles of polycyclic aromatic hydrocarbons (PAHs) as soot precursors in the sooting process have been investigated in numerous works [1][2][3][4][5][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. In 1997, Vander Wal et al [13] suggested that the appearance of a ''dark'' region separating the PAH-and soot-containing regions was caused by reduced number densities of both initiated soots and large soot precursors using simultaneous laser-induced fluorescence (LIF) and laser-induced incandescence (LII) detection.…”
Section: Introductionmentioning
confidence: 99%